Change of heart a novel - Picoult, Jodi (New York : Atria Books, 2008)
One moment June Nealon was happily looking forward to years full of laughter and adventure with her family, and the next, she was staring into a future that was as empty as her heart. Now her life is a waiting game. Waiting for time to heal her wounds, waiting for justice. In short, waiting for a miracle to happen. For Shay Bourne, life holds no more surprises. The world has given him nothing, and he has nothing to offer the world. In a heartbeat, though, something happens that changes everything for him. Now, he has one last chance for salvation, and it lies with June's eleven-year-old daughter, Claire. But between Shay and Claire stretches an ocean of bitter regrets, past crimes, and the rage of a mother who has lost her child.--From publisher description.
Keywords: Murderers; Transplantation of organs, tissues, etc; Repentance